Pilot‐Scale Evaluation of pH‐Based Control of Single Stage Deammonification Processes for Sidestream Treatment. (1st February 2017) - Graham, David M.; Jolis, Domènec
ABSTRACT: : Pilot scale sidestream reactors, utilizing a pH‐based control strategy, were operated at the San Francisco Public Utilities Commission (SFPUC), Southeast Plant (SEP) for the biological treatment of anaerobically digested sludge centrate using combined partial nitritation/anaerobic ammonium oxidation (anammox) as the main nitrogen removal pathway. Reactors were setup to functionally simulate two full‐scale commercial processes common to the industry using nonproprietary, flexible, pH‐based process control strategy. Results demonstrated that comparable full‐scale loading rates and removal efficiencies can be reached for different reactor configurations while maintaining stable process performance using this relatively simple control strategy.